2015
DOI: 10.1136/bmjopen-2015-008614
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the motivation and performance of community health volunteers involved in the delivery of health programmes in Kampala, Uganda: a realist evaluation

Abstract: ObjectivesThis paper presents the results of a realist evaluation that aimed to understand how, why and under what circumstances a Red Cross (RC) capacity-building intervention influences the motivation and the performance of RC community health volunteers involved in the delivery of an immunisation programme in Kampala, Uganda.MethodGiven the complexity of the intervention, we adopted realist evaluation as our methodological approach and the case study as our study design. Data collection included document re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Indeed, the programme theory that explains how and why the volunteerism intervention is expected to produce outcomes should be developed ideally both from the literature and the voice of the main stakeholders (programme designers, managers and volunteers). Drawing on a programme theory that is sensitive to context and tested by empirical studies is more likely to lead to the development of effective interventions when aiming to improve motivation and performance of CHVs [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the programme theory that explains how and why the volunteerism intervention is expected to produce outcomes should be developed ideally both from the literature and the voice of the main stakeholders (programme designers, managers and volunteers). Drawing on a programme theory that is sensitive to context and tested by empirical studies is more likely to lead to the development of effective interventions when aiming to improve motivation and performance of CHVs [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scope of the most recent RE conference in Brisbane in 2017 included realist research as did the recently published reference work Doing Realist Research (Emmel et al 2018). This refl ects the broader application of RE in global health research, for instance in research on policy implementation, accountability (Van Belle 2014), programme implementation (Mukumbang et al 2018(Mukumbang et al , 2016, hospital management (Marchal 2011), district management (Kwamie 2016), capacity development (Prashanth et al 2014), and health volunteerism (Vareilles et al 2015).…”
Section: From Realist Evaluation To Realist Researchmentioning
confidence: 99%
“…These findings have implications for developing strategies that ensure supportive supervision and strengthening community ties, establishing a fair recognition and reward system, and providing opportunities for training and career enhancement for health staff. While many studies focused on highly-performing workers and institutions, or on specific cadres of workers e.g., community health volunteers to identify what motivations and mechanisms drive good performance (18,37,(44)(45)(46)(47), our study assessed how motivation worked among different cadres of PHC workers (doctors, nurses, midwives, and CHEWs) in a dynamic institutional environment generated by changing health sector reform policy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing interest in the drivers and mechanisms of work motivation, only three realist evaluation studies of mechanisms of workforce motivation were identified, two of which drew on selfdetermination theory to research motivation in autonomous community health volunteers in Uganda (18) and in top-performing community health teams in El Salvador (19) respectively. The third study combined the Herzberg's two-factor theory of needs with the person-environment fit theory to identify mechanisms of employee turnover in Ethiopia (20).…”
Section: What Is Work-related Motivation?mentioning
confidence: 99%